The Density Effect in (W-S-W) Wood Connections with Internal Steel Plate and Passive Protection under Fire - Silva, Lino (2019)
The main objective of this work is to understand the fire behaviour of unprotected wood-to-wood connections with internal steel plate (W-S-W) in comparison with connections using passive protection with gypsum plasterboard. Passive fire protection uses systems that help prevent the spread of fire. Analytical methodologies according Eurocode 5 part 1-1 were used to the designed connections in different wood densities material. After that, to predict the fire exposure and the connection capacity a computational modelling was performed. Results of the temperature field and the char layer formation, for unprotected and protected members, were compared. Two different cross sections, only in wood or in wood-steel, were chosen to verify the evolution of charring rate effect.